Interpreting the knowledge map of digital library research (1990-2010) - Nguyen, Hoang Son (WILEY-BLACKWELL, 111 RIVER ST, HOBOKEN 07030-5774, NJ USA, 2017)
A knowledge map of digital library (DL) research shows the semantic organization of DL research topics and also the evolution of the field. The research reported in this article aims to find the core topics and subtopics of DL research in order to build a knowledge map of the DL domain. The methodology is comprised of a four-step research process, and two knowledge organization methods (classification and thesaurus building) were used. A knowledge map covering 21 core topics and 1,015 subtopics of DL research was created and pro-vides a systematic overview of DL research during the last two decades (1990–2010). We argue that the map can work as a knowledge platform to guide, evaluate, and improve the activities of DL research, education, and practices. Moreover, it can be transformed into a DL ontology for various applications. The research method-ology can be used to map any human knowledge domain; it is a novel and scientific method for producing comprehensive and systematic knowledge maps based